2014
DOI: 10.4238/2014.january.10.12
|View full text |Cite
|
Sign up to set email alerts
|

Thunbergia laurifolia extract minimizes the adverse effects of toxicants by regulating P-glycoprotein activity, CYP450, and lipid metabolism gene expression in HepG2 cells

Abstract: ABSTRACT. Thunbergia laurifolia (TL) is widely used as an antidote in Thai traditional medicine against toxic substances such as alcohol, pesticides, arsenic, and strychnine. We found that the lyophilized form of TL in 80% ethanol possessed the antioxidant levels within the range 23,163.9 ± 1457.4 Trolox equivalents mM/kg dry mass and 899.8 ± 14.5 gallic acid equivalents mM/kg dry mass using the oxygen radical absorbance capacity assay and the Folin Ciocalteu phenol assay, respectively. TL extract (TLE) at a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“… 44 Interestingly, PPARγ has also shown to regulate LRP1 and P-gp expressions. 45 , 46 In vivo and in vitro studies demonstrated treatment with the PPARγ activators cilostazol, a selective phosphodiesterase 3 inhibitor, and Thunbergia laurifolia , widely used as an antidote, to upregulate hepatic LRP1 protein expression in vivo 45 and P-gp activity in vitro, 46 respectively. Thus, enhanced LRP1 and P-gp efflux function by oleocanthal could also be mediated, at least in part, by activating PPARγ.…”
Section: Resultsmentioning
confidence: 99%
“… 44 Interestingly, PPARγ has also shown to regulate LRP1 and P-gp expressions. 45 , 46 In vivo and in vitro studies demonstrated treatment with the PPARγ activators cilostazol, a selective phosphodiesterase 3 inhibitor, and Thunbergia laurifolia , widely used as an antidote, to upregulate hepatic LRP1 protein expression in vivo 45 and P-gp activity in vitro, 46 respectively. Thus, enhanced LRP1 and P-gp efflux function by oleocanthal could also be mediated, at least in part, by activating PPARγ.…”
Section: Resultsmentioning
confidence: 99%
“…A previous report exhibited an increase of P-glycoprotein and a decrease in some cytochrome P450 isoenzymes such as CYP2E1 in HepG2 cells treated with T. laurifolia. 34 P-glycoprotein expressed in hepatocytes and the bloodbrain barrier 35 function as a biological barrier by extruding toxins and xenobiotics out of cells. In the brain, P-glycoprotein did not only increase the efflux but also inhibited the influx of the drug across the blood-brain barrier of nonhuman primates.…”
Section: Resultsmentioning
confidence: 99%
“…It functions as a transporter via excretion of drugs, toxic agents, and xenobiotics from cells. Several natural compounds, dietary phytochemicals, and herbal medicines have the ability to modulate P-gp function and cause effects such as drug-drug, herb-drug, and herb-toxicant interactions [45]. In this study, P-gp expression in UACC732 cells treated with lipoproteins was assessed using flow cytometry.…”
Section: Discussionmentioning
confidence: 99%